Global Economic Prospects and the Developing Countries 1991 - World Bank (Washington, DC: World Bank, 2019)
This year’s report focuses on trade in primary commodities. Chapter 1 reviews structural factors affecting the world economy, including interdependences between industrial and developing economies and on how this has helped shape economic growth and development. Chapter 2 explores this issue further with a detailed analysis of the international market in primary commodities. Chapter 3 reports on the state of the world economy today and examines the challenges it faces in the coming decade. Chapter 4 lays out several scenarios for the world economy and prospects for development in the 1990s.